Age- and sex-specific normative values for muscle mass parameters in 18,625 Brazilian adults - Coelho-Júnior, Hélio José; Marques, Fillipi Lopes; Sousa, Caio Victor; Marzetti, Emanuele; Aguiar, Samuel da Silva (Frontiers in Public Health, 2024)
Background: The present study aimed to provide age-and sex-specific normative values for muscle mass parameters in Brazilian adults. Methods: Data pertaining to Brazilian adults (18+ years) who attended a nutritional clinical between January 2018 and July 2022 were analyzed. Muscle mass parameters were assessed using a bioimpedance digital scale (InBody 230, GBC BioMed NZ).Assessments were conducted under standard conditions, with participants refraining from physical exercise for 96 hours and from eating or drinking (including water) for 8 hours before evaluations.Results: A total of 18,625 Brazilian adults were analyzed. Normative values for absolute and relative (height, m 2 ) muscle mass and appendicular muscle mass (ASM) were found. In addition, specific agerelated changes in muscle mass parameters were observed. In women, muscle mass peaks between the ages of 40-49 before gradually declining at an average rate of 5.7% per decade from the sixth decade of life onwards. ASM reaches its peak earlier, during the third decade of life, and started to decline later, from 50-59 years. In contrast, absolute and ASM peaked at 40-49 years and declined from the sixth decade of life in men. Both sexes displayed a slightly higher decline in ASM than in muscle mass (13% vs 12%). Conclusions: The present study provided normative values for absolute and relative muscle mass and ASM in Brazilian adults. Furthermore, important specific age-related changes in muscle mass parameters were observed. These data have public health implications and might serve as reference tables to guide health professionals.